Bioactive Metabolites Profile of Methanol Flower and Seed Extracts of Clitoria ternatea (L.) - Sulaikal Beevi I.; Palavesam, A. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Since ancient times, plants and plant products were used against numerous diseases. In this context, Clitoria ternatea (C. ternatea) was used for the various treatments of infectious diseases as a therapeutic role containing various phytochemical, antibacterial and antioxidant properties. The methanol flower and seed extracts of C.ternatea were analysed for antibacterial activity against Helicobacter pylori (H. pylori) using the agar well diffusion method. However, the probe of the antibacterial activity in both the methanol flower and methanol seed showed more or less the same zone of inhibition at 200 µg/ml. Furthermore, antioxidant properties were analysed by DPPH (1, 1-diphenyl-2-picrylhydrazyl) radical scavenging activity and reducing power assay. Results on the DPPH assay showed better results in the methanol flower (42.79±0.0819) extract than methanol seed extract (37.41±0.0265) 200µg/ml. Likewise, the reducing assay manifested in the extract of methanol flower (0.90737±0.00375) was supremacy. Moreover the High resolution liquid chromatography-mass spectrometry (HRLCMS) analysis of methanol flower and seed extract of C. ternatea contained 32 and 51 major bioactive compounds, respectively in positive and negative modes. In light of the study, the extracts of methanol flower and seed extract of C. ternatea are utilized in the mode of action against H. pylori. The methanolic flower and seed extracts authenticated the presence of extensive identified and unidentified phytochemicals in C. ternatea and through more light on the important bioactive compounds to be explored for medicinal applications in future research.